Organizational wrongdoing as the "foundational" grand challenge : definitions and antecedents - Gabbioneta, Claudia; Clemente, Marco; Greenwood, Royston (Research in the sociology of organizations, 2023)
Media coverage consistently features examples of organizations engaging in unethical or illegal behavior. Given its potential to impact and even damage established institutions, organizational wrongdoing deserves to be closely monitored and more carefully examined. Drawing attention to the theoretical and empirical relevance of this topic, this first instalment in a double volume of Research in the Sociology of Organizations consolidates and extends knowledge of this important subject and highlights potential directions for future research. Exploring the definitions and antecedents of organizational wrongdoing, chapters in this first volume probe the role of social control agents in drawing the line between rightful and wrongful behavior, examine the mechanisms and processes through which instances of wrongdoing turn into a scandal, and consider the antecedents of organizational wrongdoing which have received increasing attention in academic research in recent years but that still deserve further analysis. Taken individually as well as together, the two volumes that comprise Organizational Wrongdoing as the"Foundational" Grand Challenge provide a major touchstone for scholars interested in understanding recent developments and exciting new directions in the study of organizational wrongdoing.